La gestión de servicios municipales y la satisfacción de usuarios de la zona urbana del distrito de Marcabal, provincia Sánchez Carrión, año 2018 - Morillo Fernández, Estéfani Carin (2018)
The objective of this research is to determine the relationship between the management of municipal services and the satisfaction of users in the urban area of the district of Marcabal, Sánchez Carrión province, year 2018. The problem was stated in the following way: How does municipal services management relate to satisfaction of users in the urban area of the district of Marcabal, Sánchez Carrión province, year 2018? being the respective hypothesis: The management of municipal services is positively related to the satisfaction of users in the urban area of the district of Marcabal, Sánchez Carrión province, year 2018. The population of study was made up of the 132 representatives of families that live in the same number of houses in the urban area of the district of Marcabal, whose sample was 98, to whom the technique of the survey was applied with its respective instrument, which was the questionnaire; In addition, an interview was applied. The research design was non-experimental, the descriptive design transeccional or transversal type correlational. Among the most relevant results was that the relationship between the management of municipal services and user satisfaction is positive according to the Pearson correlation coefficient (r = 0.728); which indicates that a better or weaker management, greater or lesser satisfaction. Observing in the present case, that both variables qualify at a regular level. Therefore, it was recommended that the District Municipality of Marcabal develop a strategic planning based on the preparation of plans, regulations and manuals that show the vision of the future aimed at improving the management of services, which should be the objective of each area in charge of provide the services. This in order to make the population that uses the services feel as satisfied as possible.